Effectiveness of teaching methods and motor abilities: an experimental study on football passing abil-ity - Arsil, Arsil; Okilanda, Ardo; Antoni, Despita; Fakhrur Rozi, Muhammad; Saputra, Mardepi; L Mortejo, Alonzo; Anggara Suganda, Mikkey; Suryadi, Didi (Retos (Madrid), 2024)
The low score of football passing ability among students is a problem in this topic. Therefore, efforts to improve the quality of the learning process are an effort to increase students' mastery of football passing abilities through teaching methods of philanesia and parts by first looking at students' motor skills. This research aims to determine the effectiveness of teaching methods and motor skills on passing ability in soccer games. The design used in this research is an experimental method using a 2x2 factorial design. The research subjects were FIK UNP students, using a cluster random sampling technique so that 24 students were sampled. Next, data analysis was assisted using the SPSS 26 application. The research results showed that the overall method and motor skills provided a significance value (0.000 < 0.05). Furthermore, the philanesia method and motor skills provide significance values (0.013 < 0.05). The results of the ANOVA test show a significance of 0.001 < 0.05. This data proves that there is a significant difference in the influence of the overall method and the philanesia method with low and high motor skills on the results of soccer passing ability. Based on these results, it can be concluded that both the overall method and the philanesia method with motor skills provide significant effectiveness in improving students' soccer passing ability. However, the football passing ability of the group of students who were opened using the overall method produced better results than the group of students who were opened using the philanesia method. Keywords: Teaching methods, motor skills, overall methods, philanesia methods , and football passing abilities